Ujala class 2 feroz sons urdu series - Shazia, Islam (Feroz sons Lahore, 2004)
Ujala for Class 2 is a popular Urdu textbook series used in Pakistani schools. It's designed to build upon the foundation laid in Class 1, further developing reading, writing, and comprehension skills.